2001
DOI: 10.1364/ao.40.006136
|View full text |Cite
|
Sign up to set email alerts
|

CO_2 imaging with saturated planar laser-induced vibrational fluorescence

Abstract: We present new vibrational (infrared) planar laser-induced fluorescence (PLIF) imaging techniques for CO(2) that use a simple, inexpensive, high-pulse-energy transversely excited atmospheric CO(2) laser to saturate a CO(2) absorption transition at 10.6 mum. Strong excitation by use of a CO(2) laser provides increased signal levels at flame temperatures and simplifies image interpretation. Because rotational energy transfer and intramodal vibrational energy transfer are fast, vibrational distributions can be ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 25 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…This effort was followed up by the same group and complemented with CO 2 . [24][25][26] The number of detected species was then extended to smaller hydrocarbons by Li et al 27 For point measurements, polarization spectroscopy of CO 2 was demonstrated by Roy et al 28 and followed up by Alwahabi et al 29 who also compared LIF and polarization spectroscopy in a later work. 30 Taking advantage of the coherent nature of polarization spectroscopy, measurements of nascent CO 2 and H 2 O in a flame was published by Li et al 31 , but two-dimensional measurements in background-challenging environments were still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This effort was followed up by the same group and complemented with CO 2 . [24][25][26] The number of detected species was then extended to smaller hydrocarbons by Li et al 27 For point measurements, polarization spectroscopy of CO 2 was demonstrated by Roy et al 28 and followed up by Alwahabi et al 29 who also compared LIF and polarization spectroscopy in a later work. 30 Taking advantage of the coherent nature of polarization spectroscopy, measurements of nascent CO 2 and H 2 O in a flame was published by Li et al 31 , but two-dimensional measurements in background-challenging environments were still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed laser-induced fluorescence (LIF) diagnostics using vibrational excitation of CO and CO 2 in the infrared have been demonstrated previously for spatially resolved gasdynamic measurements [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Excitation at 2.7 µm is chosen as an optimized scheme for the current setup, because it provides relatively strong absorption cross section, while the laser absorption by the air along the beam path is not so severe. Other excitation schemes for CO 2 PLIF detection can be found in [29][30][31][32][33]. As a proof of concept, quantitative measurements of both CO and CO 2 over a Pd catalyst during catalytic CO oxidation have been carried out to demonstrate the high spatial and temporal resolution of the two techniques for studies of gas phase in catalysis.…”
mentioning
confidence: 99%